Engineering of Aeromonas caviae Polyhydroxyalkanoate Synthase Through Site-Directed Mutagenesis for Enhanced Polymerization of the 3-Hydroxyhexanoate Unit - Harada, Ken; Kobayashi, Shingo; Oshima, Kanji; Yoshida, Shinichi; Tsuge, Takeharu; Sato, Shunsuke (Frontiers in Bioengineering and Biotechnology, 2021)
Polyhydroxyalkanoate (PHA) synthase is an enzyme that polymerizes the acyl group of hydroxyacyl-coenzyme A (CoA) substrates. Aeromonas caviae PHA synthase (PhaCAc) is an important biocatalyst for the synthesis of a useful PHA copolymer, poly[(R)-3-hydroxybutyrate-co-(R)-3-hydroxyhexanoate] [P(3HB-co-3HHx)]. Previously, a PhaCAc mutant with double mutations in asparagine 149 (replaced by serine [N149S]) and aspartate 171 (replaced by glycine [D171G]) was generated to synthesize a 3HHx-rich P(3HB-co-3HHx) and was named PhaCAc NSDG. In this study, to further increase the 3HHx fraction in biosynthesized PHA, PhaCAc was engineered based on the three-dimensional structural information of PHA synthases. First, a homology model of PhaCAc was built to target the residues for site-directed mutagenesis. Three residues, namely tyrosine 318 (Y318), serine 389 (S389), and leucine 436 (L436), were predicted to be involved in substrate recognition by PhaCAc. These PhaCAc NSDG residues were replaced with other amino acids, and the resulting triple mutants were expressed in the engineered strain of Ralstonia eutropha for application in PHA biosynthesis from palm kernel oil. The S389T mutation allowed the synthesis of P(3HB-co-3HHx) with an increased 3HHx fraction without a significant reduction in PHA yield. Thus, a new workhorse enzyme was successfully engineered for the biosynthesis of a higher 3HHx-fraction polymer.